2001
DOI: 10.1177/002215540104900308
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin I Expression in Mast Cells of Normal Human Tissues, Systemic Mast Cell Disease, and a Human Mast Cell Leukemia Cell Line

Abstract: Synaptotagmin I (STG I) is a Ca(2+) sensor and one of the synaptic vesicle proteins that mediate exocytosis. To determine the mechanism of release of large granules from mast cells, we studied by immunohistochemistry the presence of STG I in mast cells in normal human tissues simultaneously with the mast cell markers mast cell tryptase (tryptase) and c-kit. The tumor cells of systemic mast cell disease (SMCD) and a human mast cell leukemia cell line (HMC-1) were also examined. Human mast cells in normal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The expression of SYT I increases in stimulated human mast cells as was demonstrated by immunohistochemistry (29). In this study, we observed that the expression of SYT I was elevated in resting SMC (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The expression of SYT I increases in stimulated human mast cells as was demonstrated by immunohistochemistry (29). In this study, we observed that the expression of SYT I was elevated in resting SMC (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Another protein known to play an important role in the exocytosis of mast cells is SYT I (28,29), which acts as one of the Ca 2ϩ sensors in the synaptic vesicle and mediates exocytosis (42). The expression of SYT I increases in stimulated human mast cells as was demonstrated by immunohistochemistry (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…FcR stimulation initiates signaling cascades including the phospholipase C␥1, PI3K and MAPK pathways (7) with subsequent calcium raise in the cytosol (8,9). The increase in intracellular calcium levels, sensed synaptotagmins (SYT) 4 (10,11), is a prerequisite for degranulation mediated by SNARE (soluble NSF attachment receptor) complex formation, which is crucially involved in the fusion of vesicle and plasma membrane. SNARE complexes are composed of small membrane-bound proteins, such as VAMPs (vehicle-associated membrane proteins), SNAPs (synaptosome-associated proteins), and STX (syntaxins) (7,12,13).…”
mentioning
confidence: 99%
“…Previous studies suggested that synaptotagmin 1 is expressed in mast cells and regulates mast cell function (Baram et al, 1999;Baram et al, 1998;Kimura et al, 2001). The role of…”
Section: +mentioning
confidence: 99%